Academic Majors Recommendation Using Analytical Hierarchy Process and Multi-Objective Optimization on the Basis of Ratio Analysis - Jaya, Ivan; Andayani, Ulfi; Rizky, Ayu Dwi; Lubis, Juanda Hakim (UIN Sumatera Utara, 2020)
In determining an academic majors, the mere information about the departments is not sufficient as the base of taking the decision as one would only know popular majors without being aware of his/her potential. There are also limited recommendations obtained through counseling guidance. By using the Analytical Hierarchy Process (AHP) and Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) methods, prospective students get the recommendations of academic majors by putting their preference criteria for the majors. The criteria used are affordable study costs, accreditation of majors, department facilities, student potential to the majors, student interest in majors, future goals, parental advice, self-desire, peer influence, report card scores, previous achievements, passing grade majors and length of study. The Spearman's Rank Correlation method was used to determine the results of the correlation ranking recommendations from the teacher (guidance and counseling teacher) and the system where the weights obtained from the teacher (guidance and counseling teacher) and from the students who filled it through the system. Based on the correlation of the system ranking with the guidance and counseling teacher ranking to 25 students majoring in Natural sciences class XII, the average value of accuracy was 88% with a standard deviation of 0.13. As for the students majoring in social sciences, the average value of accuracy was 97% with a standard deviation of 0.03. From this research, it can be concluded that the Analytical Hierarchy Process (AHP) and Multi Objective Optimization on the basis of Ratio Analysis (MOORA) methods can be used in helping to solve decision-making problems in the recommendation system of academic majors.